The inheritance culture of Thai Chinese people in Doi Mae Salong, Chiang Rai - Nueakwan Buaphuan, เหนือขวัญ บัวเผื่อน （潘佳丽） (Dusit Thani College Journal, 2018)
This research aimed to study the use of communication language and the inheritance culture of Thai-Chinese settlers in Doi Mae Salong, Chiang Rai province, located in the northern part of Thailand, adjacent to Myanmar for studying language and culture of Thai-Chinese descent on Doi Mae Salong, Chiang Rai, using 50 interviewees. The research found that there is only Yunnan Chinese in the household communication. The 86 percent used Mandarin and used Yunnan 14 percent. The language of daily life, they use Thai language and both of Chinese languages (Mandarin and Yunnan) in 88 percent. There is no formal language inheritance. At present, 64% of the population is promoting the young generation to get the knowledge of the Chinese language. They want to Inherit of language for new generation in the future.